Halogenated symmetrical tetraazapentacenes: synthesis, structures, and properties - Engelhart, Jens U.; Paulus, Fabian; Schaffroth, Manuel; Vasilenko, Vladislav; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (The journal of organic chemistry, 2016)
We herein describe the synthesis and property evaluation of several brominated and chlorinated tetraazapentacenes. The targets were obtained by thermal condensation of 2,5-dihydroxyquinone with 4,5-dichloro-, 2,6-dichloro-, and 4,5-dibromo-1,2-phenylenediamine, followed by oxidation with hot acidic dichromate. Double alkynylation, reductive deoxygenation, and subsequent oxidation using MnO2 furnishes the target compounds. Absorption spectra, electrochemistry, and single crystal structures of the targets are reported. The 1,4,8,11-tetrachlorotetraazapentacene (1,4,8,11-tetrachloroquinoxalino[2,3-b]phenazine) carrying its chlorine atoms in the peri-positions packs in a herringbone type arrangement, while the isomer (2,3,9,10-tetrachloroquinoxalino[2,3-b]phenazine, with the chlorine atoms in the east and west positions) packs in one-dimensional stacks. In all cases, the reduction potentials and the calculated LUMO-positions are decreased by the introduction of the halogen atoms.